Electrocardiographic And Echocardiographic Profile of Dilated Cardiomyopathy Patients Attending Tertiary Care Hospital in Vadodara - Rana, Himanshu M; Chavda, Parag; Rathod, Chirag C; Mavani, Meera (National Journal of Community Medicine, 2015)
Background: Dilated cardiomyopathy is one of the important causes of congestive heart failure and attributes to 25% of all cases of CHF. Moreover, in majority of cases with DCM, no specific etiology is known. The increasing incidence of DCM is also associated with sig- nificant morbidity and mortality. So, the current study aimed at un- derstanding the electrocardiographic and echocardiographic profile of DCM patients coming to tertiary care hospital in Vadodara. Methods: A descriptive cross sectional study was conducted among 180 patients with dilated cardiomyopathy from the year 2011 to 2014. ECG and 2D Echocardiography was done among all these patients using standard techniques. The data entry and analysis was done in Microsoft excel sheet. Results: Among the 180 study participants having DCM, almost all patients showed changes in ECG and 2D Echocardiography. The most common ECG changes observed were ST-T changes (93.8%) followed by sinus tachycardia (63.3%). The most common 2D Echo findings observed were left ventricular diastolic dimension > 5.2cm (93%) followed by left ventricular systolic dimension >3.9cm (91%) and reduced left ventricular contractility (85%). Conclusion: Regular echochardiographic and electrocardiographic screening of patients with dilated cardiomyopathy is very important to identify and prevent complications among them.